(untitled) (LEGAL DIALOGICA, 2025)
This study aims to identify and analyze how the comparison of criminal sanctions regulations for environmental crimes by corporations in Law Number 32 of 2009 concerning Environmental Protection and Management and the New Criminal Code. As well as to identify and analyze how the differences in the principles of criminal liability in the UUPPLH and the New Criminal Code. This study uses a normative legal research method with a legislative approach and a conceptual approach. This study values ​​​​novelty through a comparative approach between Articles 344 and 345 of the New Criminal Code and Articles 98 and 99 of the UUPPLH in the context of overcoming environmental crimes by corporations. The results of this study indicate a difference between criminal sanctions for environmental crimes in Articles 98 and 99 of Law Number 32 of 2009 concerning Environmental Protection and Management with Articles 344 and 345 of the New Criminal Code. The difference in the principles of criminal liability in the Environmental Management Law (PPLH) and the New Criminal Code is that Articles 98 and 99 of the PPLH Law apply the principle of strict liability in the application of criminal liability, while Articles 344 and 345 of the New Criminal Code emphasize the principle of culpability. The author recommends that regulations between the PPLH Law and the New Criminal Code be harmonized to avoid dualism in the application of environmental criminal law. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis Bagaimana perbandingan pengaturan sanksi pidana terhadap kejahatan lingkungan oleh korporasi dalam Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup dan KUHP Baru. Serta Untuk mengidentifikasi dan menganalisis Bagaimana perbedaan asas pertanggung jawaban pidana dalam UUPPLH dan KUHP Baru. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendeketan perundang-undangan dan pendekatan konseptual. Penelitian ini nilai kebaruan melalui pendekatan perbandingan antara Pasal 344 dan 345 KUHP Baru dan Pasal 98 dan 99 UUPPLH dalam konteks penanggulangan kejahatan lingkungan oleh korporasi. Hasil penelitian ini menunjukkan adanya perbedaan antara sanksi pidana terhadap kejahatan lingkungan dalam pasal 98 dan 99 Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup dengan Pasal 344 dan 345 KUHP Baru. Perbedaan asas pertanggungjawaban pidana dalam UU PPLH dan KUHP Baru, pada Pasal 98 dan 99 UU PPLH menerapkan asas strict liability dalam penerapan pertanggungjawaban pidana, sementara pasal 344 dan 345 KUHP Baru lebih menekankan asas culpability. Rekomendasi yang diberikan oleh penulis adalah diperlukan adanya harmonisasi peraturan antara UU PPLH dan KUHP Baru agar tidak terjadinya dualisme dalam penerapan hukum pidana lingkungan.